Design and Performance Testing of a Battery Management System (BMS) for Electric Quadcopter Vehicles: Efficiency and Safety of LiFePO4 Batteries - Umi Anis Roisyatin; Mochammad Bilal Al Kahvi (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
The quadcopter Flying Electric Vehicle (KLT) is an emerging technology that has great potential for various applications. The battery is one of the important components in the quadcopter KLT, and the Battery Management System (BMS) plays an important role in maintaining the performance, safety, and life of the battery. This study aims to determine the wiring design and test the performance of the BMS on a quadcopter flying electric vehicle. The study uses a quantitative approach with a descriptive type. By designing a Battery Management System (BMS) for flying electric vehicles and then testing the BMS to find out its effect on the performance of electric motors and safety on batteries. Then after the battery design process and testing, a BMS monitor display will be obtained during standby mode and work mode. The test results, namely when the battery management system is on standby, open throttle BLDC 25%,50%,75%,100% and open start throttle show that the battery is in good condition and has sufficient capacity. The battery voltage is within the normal range, the battery current does not flow, the battery power is not used, the average cell voltage is normal, and the remaining battery capacity is almost full. Jikong's BMS is functioning properly and the battery is in good condition. The planning of the battery management system (BMS) on the quadcopter flying electric vehicle was successfully made with adjustments to the Battery LifePo4 used